A Comparative Study of Pt Depositing Methods (Chemical Reduction vs Photo-Assisted Deposition) onto TiO2 Nanoparticles for Hydrogen Photo-Production - Ratnawati Ratnawati; Slamet Slamet; Viona Wongso; Jarnuzi Gunlazuardi; Muhammad Ibadurrohman (Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
In this paper, we report a comparative study on two methods (chemical reduction and photo-assisted deposition) of incorporating Pt onto TiO2 nanoparticles (TNP) for H2 generation. The phase structure of the photocatalysts was scrutinized utilizing TEM and XRD. The degree of dispersion of Pt on the TNP was calculated by a pulse chemisorption technique using TPDRO equipment. The results provided by TEM imagery, EDX spectra, elemental mapping, and AAS confirmed the successful deposition of Pt on TNP. XRD patterns confirmed an anatase and rutile crystallite structure, while UV-Vis spectra showed reduction of the bandgap from a typical value of 3.2 eV to ca. 2.9 eV. It was found that there is a correlation between the deposited Pt and dispersed Pt on the TNP with H2 generation. The chemical reduction method offered a higher degree of Pt deposition, resulting in a 2.75 times larger amount of deposited Pt compared to photodeposition. This feature is perceived to contribute a higher H2 yield (3,283 µmol) at 1 w% of Pt loading.